Changes in endotracheal tube cuff pressures and incidence of post-operative sore throat while using different inflating agents - Aziz, Lutful; Zafor, Iqbal Mohammad; Nimmi, Nahida Parveen; Farhana, Akhter Kazi; Uddin Al, Azad Salah (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background & Aims: Post-operative sore throat is one of the minor complications after general anaesthesia with endo tracheal intubation. Although short lasting and self-limiting, it creates an uncomfortable situation for patient. Diffusion of Nitrous Oxide (N20) into endotracheal tube (ETT) cuffs and increase intra cuff pressure causes this. Different inflating agents have been studied to see the incidence of intra cuff pressure changes. This study was performed to see the post extubation tracheal mucosal changes and post-operative sore throat after using N20 in Oxygen as ETT cuff with direct visualization of the tracheal mucosa just after tracheal extubation. Methods: Institutional ethical committee approval and informed written consent were obtained, 50 patients, undergoing elective surgery under general anaesthesia, were enrolled. Patients were randomly allocated in two groups of 25. In Group A, the ETT cuff was inflated with air, in Group B, cuff was inflated with 67% N₂0 in oxygen. The cuff pressure was kept around 30 cm H₂0 and was measured every 10 minutes. The condition of the trachea was seen using fibreoptic bronchoscope and a grading was done. All the data was collected & statistical analysis performed. Results: The frequencies of pain, difficulty in swallowing, and hoarseness of voice at the recovery room within the first two hours after anaesthesia were lowest in Group B than Group A and significantly reduced within 24 hours. Perioperatively cuff pressure change in group A was significantly high and in group B it was minimum. Bronchoscopic view of larynx and trachea showed 64 % normal. 22% was erythematous, 10% was oedematous in group B. In group A it was 28%, 46% and 24%. Conclusions: It is evident, that N₂0 in 0₂ filled ETT cuff reduces the incidence of postoperative sore throat. It is proposed that the difference was produced due to no or minimum diffusion of N₂0 in N₂0 with 0₂ filled ETT cuff, subsequently no significant intra cuff pressure changes per operatively. J Bangladesh Coll Phys Surg 2024; 42: 12-18